Pharmacognistic Study of Medicinal Plant (International Journal of Scientific Research in Science and Technology, 2025)
Herb being used as culinary and traditional medicine from ancient time.Fenugreek also has Trigonella foenum-graceum is also known as methika (family Papillionaceae)is an annual an exceptional nutritional and pharmaceutical profile. It has substantial amount of fibre, phospholipid, glycolipids, oleicacid, linoleicacid, choline, vitaminsA, B1, B2, C, nictotinic acid, niacin The plant grows upto 60 cm in height and its seeds are golden-yellow rhomboidal-shaped. P-Hytochemical standardization parameters such as moisture content, total ash, alcohol and water soluble extractives were determined Vitex negunda of family Verbenaceae is attractive evergreen tree of subtropical and warm region of India. In recent times, focus on plant research has increased all over the world and a large body of evidence has collected to show immense potential of medicinal plants used in various traditional system. Over the last few years, researchers have aimed at identifying and validating plant derived substances for treatment of various disease.,. A comprehensive overview of pharmacognistic analysis of fenugreek is given here. Here we have many parameters to study like ash value, moisture content, swelling and foaming index,and many other parameters. We are discussing about various chemical constituents. Here we have the TLC analysis carried out
Keywords: methika; extractive value; TLC analysis